(untitled) (Academic Journal of Internal Affairs, 2025)
Aim: The authors of the two-part study present a recently emerging field of science – epigenetics – based on published literature data, illustrating the process of gene expression through traditional genetic and epigenetic examples, as well as results achieved in the field of forensic sciences – genetics and dactyloscopy. The first study presents the basics of epigenetics, intergenerational trauma, and the legal and ethical aspects of epigenetics. Methodology: The study processes and synthesizes academic papers from a wide range of sciences, including genetics, history, ethics, and law. Findings: All external and internal environmental factors can cause chemical modifications in our genes, turning them on or off over time. These changes can be passed on, at least in part, to the next generation. Epigenetics research and the use of its results must comply with legal and ethical rules. Value: The study provides a comprehensive picture of the molecular background of epigenetic inheritance through literature studies and also presents a structured description of the legal and ethical concerns related to epigenetics.